Knowledge of nutrition during pregnancy and associated factors among antenatal mothers - Lim, Zhe Xin; Wong, Jun Leong; Lim, Poh Ying; Soon, Lean Keng (Community Health Society Malaysia (CHSM), 2018)
Background: Nutritional requirement increases during pregnancy can influence the growth, development, and health of the mother and her newborn child. Understanding the antenatal mothers’ nutrition knowledge is essential to developing effective strategies to curb malnutrition and encouraging healthier dietary behaviors. The aim of this study was to assess the level and associated factors of nutritional knowledge during pregnancy among antenatal mothers in a tertiary teaching hospital in northeast Malaysia. Materials and Methods: A cross-sectional study was done on 88 randomly selected antenatal mothers at the Obstetrics and Gynecology Clinic during their antenatal care visits. Data was collected using a pretested self-administered questionnaire between December 2015 and February 2016. The Kruskal-Wallis test was used to determine the association of selected socio-demographic variables and obstetric data with nutritional knowledge score among antenatal mothers. Results: The mean age of the participants was 32.06 ± 5.56 years. More than half (63.6%) of the antenatal mothers had good nutritional knowledge level. Higher occupational status (p=0.030) and monthly household income (p=0.016) of participants were significantly associated with higher nutritional knowledge score. Conclusion: These findings highlight the current knowledge gap that exists in antenatal mothers. It can be concluded that nutritional education ought to be intensified to address this issue.